Fiscal and Monetary Policy for The Development of Indonesian Plantation - Suharyadi Suharyadi (Universitas Islam Indonesia, 2009)
The global monetary crisis in 2007-2008 and the focus of development on climate changesmake it important to promote a healthy economic growth based on the local resources, Theeconomic crisis, which has slowed down the economic growth and has caused job losseswhich result in increasing unemployment and poverty, should alter the focus of Indonesianeconomic development in the future to be based on renewable and sustainable local resources.Indonesia is an agricultural and maritime country so these two aspects should be thecore of the growth. In agricultural culture, plantation sector is the source of sustainable economicgrowth because of its geographical, demographic, and cultural potentials. The problemsin plantation sector are the low growth of areas and productivity as well as its limitedend-products. The research findings indicated that in order to increase areas, there should bea guarantee on investment, interest rate, and little retribution or good governance. To increaseproductivity, we need a guarantee on fertilizer price, interest rate, and wages, as wellas pricing factors to avoid market distortion. This is very important relating to the economicstimulus policy which is essential to revitalize from the economic doom in the future.Keywords: plantation sector, area, productivity, investment, interest rate, and wages